Prevalence of Bacterial Meningitis in Ajdabyia City (مجلة العلوم الشاملة, 2025)
Meningitis is an inflammation of brain membranes and spinal cord. These membranes are collectively known as meninges and these membranes provide protection against external hazards and various microorganisms .This bacterial infection has high mortality rate if untreated because in this infection host defense mechanism of meninges to fight against bacteria becomes week or no more. H influenzae is the main important causative organism, especially in those who are not vaccinated and ranging in age of two months to two years . Meningitis is a serious health problem caused by a variety of pathogenic organisms that vary in age and spread. The infection could spread through the bloodstream or through the ears, nasopharynx, cranial injury, or congenital meningeal malformation . Due to acute meningeal inflammation, bacterial meningitis is associated with considerable morbidity and mortality. More than one million individuals are infected each year around the world, and it is more prevalent in developing nations such as Africa's meningitis belt. This belt runs from Senegal to Ethiopia, and it is here that the illness load is highest.